Wing vein formation in Drosophila melanogaster: hairless is involved in the cross-talk between Notch and EGF signaling pathways. - Johannes, B.; Preiss, A. (Mechanisms of Development, 2002)
Wing vein development in Drosophila is controlled by different morphogenetic pathways, including Notch. Hairless (H) antagonizes Notch target gene activation by binding to the Notch signal transducer Suppressor of Hairless [Su(H)]. Accordingly, overexpression of H phenocopies reduction of Notch activity. Deletion of the Su(H)-binding domain in H-C2 results in loss of H activity. However, overexpression of H-C2 induces formation of ectopic veins. In a screen for genetic modifiers of this phenotype, we have identified several genes involved in Notch and epidermal growth factor (EGF) signaling. Most notably veinlet, an activator of EGF signaling, acts downstream of H-C2. H-C2 positively regulates veinlet maybe through inhibition of inter-vein determinants in agreement with a model, whereby Notch and EGF signaling pathways cross-regulate vein pre-patterning.